Estudo químico-quântico da relação estrutura atividade da Indolo [2,1b] Quinazolina e seus derivados análogos contra o câncer de mama - (:unkn) unknown (Universidade Estadual de Goiás, 2008)
The biological activities of the Indolo[2,1b]quinalozine and thirty and three analogue compounds were synthesized and tested in vitro against the human breast cancer cells. The assays show that twenty and two of these compounds exhibited cytotoxic activity while other compounds are not cytotoxic. With the aim to corelate the physical chemical parameters of those compounds with the anticancer activity, quantum molecular calculations were carried out using the Density Functional Theory (DFT) with the exchange correlation functional B3LYP and the basis set 6-31G* implemented in Gaussian 03 suite of program. The descriptors obtained from the theoretical calculations were related to the anticancer activity using the multivariate statistical methods implemented in the Unscrambler 9.1 chemometrics program. The Principal Component Analysis (PCA) showed that five electronic descriptors are able to separate the compounds into two classes: active and inactive. The first component alone was responsible for the separation and describes 50% of the total variance of the original data. From the selected descriptors it is possible rationally to design new compounds for synthesis that can be more active against breast cancer cells.
Keywords: Câncer de mama; Mecânica Quântica; Funcional da Densidade (DFT); Análise de componentes principais (PCA); Breast cancer; Density functional theory (DFT); Principal component analysis (PCA); CIENCIAS EXATAS E DA TERRA::QUIMICA